Odpowiedzi

2010-04-05T13:04:40+02:00
P=d/M*RT /*M
MP=dRT //P
M=dRT/P

f=9/5c+32
f-32=9/5c /*5/9
c=(f-32)5/9

s=Vt+at²/2
s-Vt=at²/2 /*2
2(s-Vt)=at² //t²
a=2(s-Vt)/t²

F=GMm/r² /*r²
GMm=Fr² //GM
m=Fr²/GM
4 4 4
2010-04-05T13:10:00+02:00
A) P=d/MRT ==> PMRT=d ==> M= d/PRT
b) f= 9/5c+ 32 ==> 9/5c= f-32 ==> c= (5/9)*(f-32)
c) s=vt+ at²/2 ==> 2s=2vt +at² ==> at²= 2s-2vt ==> a=(2s-2vt)/t²
d) F=GmM/r² ==> Fr²=GmM ==> m=Fr²/GM
2 4 2
2010-04-05T13:11:55+02:00
A) P= d/M RT /:RT
P/RT=d/M /:d
M=P/RTd

b) f = 9/5 c + 32 /-32
f-32=9/5 c /*5/9
5/9(f-32)=c

c) s = vt + at²/2 /*2
2s=vt + at² /-vt
2s - vt = at² /:t²
2s - vt/t² = a

d) F = G Mm/r² /*r
F * r² = GMm / : GM
F * r²/GM = m
2 4 2